Working conditions for healthcare workers at a Swedish university hospital infectious disease department during the COVID-19 pandemic: barriers and facilitators to maintaining employee wellbeing - Veje, Malin; Linden, Karolina; Sengpiel, Verena; Carlsson, Ylva; Jonsdottir, Ingibjörg H.; Degl’Innocenti, Alessio; Ahlstrom, Linda; Wijk, Helle; Akerstrom, Magnus (Frontiers in Psychology, 2023)
Background Healthcare workers (HCWs) at infectious disease departments have held the frontline during the COVID-19 pandemic. This study aimed to identify barriers and facilitators to maintaining the employees’ wellbeing that may be used to increase preparedness for future pandemics within ID Departments. Methods In September 2020, a web-based survey on demographics and work environment was distributed to all HCWs at the Infectious Disease Department at Sahlgrenska University Hospital. Results were compared with a pre-COVID-19 survey from October 2019. A quantitative analysis of the overall effects of the pandemic on the working conditions of HCWs was conducted; in addition, a qualitative content analysis of open-ended responses was performed. Results In total, 222 and 149 HCWs completed the pre-COVID-19 and COVID-19 surveys (84 and 54% response rate), respectively. Overall, we found significant changes regarding increased workload, lack of emotional support in stressful work situations, and inability to recover after shifts. These factors correlated both with younger age and concern of becoming infected. The open-ended answers (n = 103, 69%) revealed five generic categories (Workload; Organizational support; Worry and ethical stress; Capability; and Cooperation and unity) with a total of 14 identified factors representing plausible individual and organizational-level barriers or facilitators to sustained employee wellbeing. Conclusion Younger HCWs as well as those expressing worries about contracting the infection were found to be particularly affected during the COVID-19 pandemic and these groups may require additional support in future outbreaks. Factors both increasing and decreasing the pandemic-induced negative health consequences for HCWs were identified; this knowledge may be utilized in the future.